Credit market competition and the gender gap: Evidence from local labor markets - Alexander Popov; Sonia Zaharia (European Central Bank (ECB), 2017)
We exploit the exogenous variation in regional credit market contestability brought on by banking deregulation in the United States to study the narrowing of the gender gap in local labor markets. We .nd that deregulation reduced the gender gap in labor force participation, as the subsequent increase in the demand for labor induced non-working women to enter the labor force. Deregulation also reduced wage inequality as women became more likely to work in the private sector, to enter high-paid "male" jobs, and to acquire higher education. Tests of contiguous MSAs sharing a state border corroborate a genuine deregulation effect.
Keywords: G28; J16; J22; 330; Bank deregulation; gender gap; labor force participation; wage inequality